Analisis Bibliometrik: Penerapan Mobile Application “Bank Sampah” sebagai Layanan Pengelolaan Sampah di Era Digital - Hs, Arifatul Azzarah; Sunusi, Putri Melinda; Nurwahyuni, Andi; Reskita, Dewiyanti; D, Nurjannah; Mustari, Muhammad Laits Meilano; Sonni, Alem Febri (KAMBOTI: Jurnal Sosial dan Humaniora, 2025)
This study examines the trends in research on the implementation of mobile waste bank applications for waste management in the digital era in Indonesia from 2019 to 2023. A bibliometric analysis was conducted using VOSviewer to identify keyword co-occurrence and the clustering of related topics. The findings reveal that research on mobile waste bank applications has seen a significant increase in publications, with a peak of 120 articles in 2022. However, a decline in publications was observed in 2023, with only 80 articles published. The most cited article in this field, "Systematic Literature Review Method for Identifying Platforms and Information System Development Methods in Indonesia" by Triandini et al., (2019), has garnered 490 citations. The analysis further identifies eight clusters with a total of 25 items, reflecting diverse themes within the application of mobile waste banks. Prominent themes include "waste bank," "digital waste management," and "waste bank system," indicating that these areas have been widely researched. However, certain topics, such as "smart waste saving," "organic and inorganic waste management," and "waste bank online systems," remain underexplored. These underrepresented themes present significant opportunities for further research. Overall, the study suggests a positive trend in research on mobile waste banks, highlighting the potential for future development and innovation in digital waste management systems. The findings provide valuable insights for future studies and the advancement of waste bank applications in Indonesia.